2014
DOI: 10.1038/emm.2014.40
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory G proteins and their receptors: emerging therapeutic targets for obesity and diabetes

Abstract: The worldwide prevalence of obesity is steadily increasing, nearly doubling between 1980 and 2008. Obesity is often associated with insulin resistance, a major risk factor for type 2 diabetes mellitus (T2DM): a costly chronic disease and serious public health problem. The underlying cause of T2DM is a failure of the beta cells of the pancreas to continue to produce enough insulin to counteract insulin resistance. Most current T2DM therapeutics do not prevent continued loss of insulin secretion capacity, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 111 publications
(145 reference statements)
1
30
0
Order By: Relevance
“…Melatonin has been proposed to reduce response to both oral and intravenous glucose and with faster deterioration of insulin secretion over time in type 2 diabetes . The MTNR1B receptor is a transmembrane G protein-coupled receptor, proposed to be a new pharmacological target for diabetes (Mulder et al, 2009;Kimple et al, 2014). The MTNR1B is expressed in β-cells, and β-cells from diabetic patients tended to have increased MTNR1B expression .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Melatonin has been proposed to reduce response to both oral and intravenous glucose and with faster deterioration of insulin secretion over time in type 2 diabetes . The MTNR1B receptor is a transmembrane G protein-coupled receptor, proposed to be a new pharmacological target for diabetes (Mulder et al, 2009;Kimple et al, 2014). The MTNR1B is expressed in β-cells, and β-cells from diabetic patients tended to have increased MTNR1B expression .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…According to previous studies, after binding to β 2 -receptor, β 2 -agonists activated several sub-units of G protein family which consequently causes glucose-stimulated and hormone-stimulated insulin secretion 13,22 . When using at dosage of 10mg/kg and 100mg/kg consecutively in 30 days, clenbuterol induced a significant decline in glucose concentrations in mice 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, it was reported that clenbuterol residues in eddible tissues were higher 2,000 times than MRLs, and the amount of clenbuterol consumed was estimated about 230-300µg 9 . Previous studies evaluated the prolonged effects of clenbuterol on animals (mice, rats, pigs) at high concentrations (20-2,000 µg/kg body weight) [11][12][13][14] , and the results showed that clenbuterol affected protein, glucose and lipid metabolism [15][16][17][18] . However, these studies were conducted for a short time.…”
Section: Introductionmentioning
confidence: 99%
“…Targets for therapeutic interventions include several members of the GPCR superfamily and their ligands as well as various GPCR-scaffolding proteins (167). Ghrelin, with its critical role in energy homeostasis, and its receptor, the GH secretagogue receptor [ghrelin receptor (GHSR1)] are of great significance for the treatment of obesity (168).…”
Section: Obesity and Diabetesmentioning
confidence: 99%